2022
DOI: 10.1159/000520705
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Clinical Factors on Low-Intensity Extracorporeal Shockwave Therapy for Erectile Dysfunction

Abstract: <b><i>Introduction:</i></b> Predictive factors for the treatment success of low-intensity extracorporeal shockwave therapy (Li-ESWT) for erectile dysfunction (ED) are still under debate. <b><i>Methods:</i></b> Li-ESWT was performed in 50 patients suffering from ED by applying 3,000 shock waves once a week over a period of 6 weeks. Treatment success was defined as an increase in the International Index of Erectile Function 5 (IIEF-5) score by ≥5 points or an Erect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Another 3 cases had improved erectile function 6 months after the treatment. In addition, the effect was significantly improved for patients with cardiovascular risk factors (p = .026) (Oginski et al, 2022). This study proves that Li-ESWT is an effective but short-term treatment method FIGURE 4 Mechanism of VED for the treatment of ED.…”
Section: Low-intensity Extracorporeal Shock Wave Therapy (Li-eswt)supporting
confidence: 53%
“…Another 3 cases had improved erectile function 6 months after the treatment. In addition, the effect was significantly improved for patients with cardiovascular risk factors (p = .026) (Oginski et al, 2022). This study proves that Li-ESWT is an effective but short-term treatment method FIGURE 4 Mechanism of VED for the treatment of ED.…”
Section: Low-intensity Extracorporeal Shock Wave Therapy (Li-eswt)supporting
confidence: 53%
“…A recently published study demonstrated an initial good response to ESWT in 50% of patients with ED after 3 months. However, this effect lasted for 6 months in only 16% of patients [28]. On the other hand, a recent systematic review reported that the effect of ESWT for ED decreased at 12-month follow-up, although overall ED improved compared to the pre-treatment situation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although some progress has been made, further research is needed to explore the effect of various risk factors on Li-ESWT therapy. (20).…”
Section: Discussionmentioning
confidence: 99%